Instant Emotional Healing: Acupressure for the Emotions - Permanent Solutions to Everyday Problems - Lambrou, Peter and Pratt, George (London Rider Books, 2000)
This book shows you how to give yourself instant relief from negative emotions. Drawing on a combination of the meridian systems of Eastern acupuncture and Western cognitive ideas, the author offers step-by-step instructions on how to use key pressure points on your body, breathing techniques and focused thought to overcome negative feelings.
Include Index, Biliography, Illustrations and Glossary.
Keywords: Acupressure -- Touch -- Therapeutic Use